Nutritional evaluation of sugarcane (Saccharum officinarum) trash as dry fodder source for cattle - RAO, S B N; GOWDA, N K S; SOREN, N M; KUMAR, M A PAVAN; AWACHAT, VAIBHAV; BHAT, S KARTHIK; PRASAD, K S; RAMACHANDRA, K S (The Indian Journal of Animal Sciences, 2019)
The present experiment was conducted in two phases. In the first phase, sugarcane (Saccharum officinarum) trash (ST), rice (Oryza sativa) straw (RS) and finger millet (Eleusine corocana) straw (FMS), and their respective diets comprising 70% dry ST, 20% paragrass (Brachiara mutica) and 10% concentrate mixture were evaluated by in vitro gas production techique (IVGPT). The gas production, DMD and OMD were less in ST followed by RS and FMS. Significantly lower acetate, propionate, butyrate, total volatile fatty acids and A:P was recorded in ST followed by RS and FMS. Similar trend was noticed in case of total mixed rations (TMR). In the second phase, ST based total mixed ration was evaluated against conventional FMS based ration. Crossbred cattle (10; average BW 318Â±19 kg) were divided into 2 groups. Group I was offered TMR comprising 70% FMS whereas in group II, FMS was replaced by ST. The digestibility of DM, OM and NFE was lower in cattle fed ST as compared to FMS. Digestible CP of the diets remained same in both groups, however, TDN value was more in case of FMS based TMR. Ca, P, Zn absorption was found to be similar in both the groups. However, Mg and Cu absorption was more in ST based TMR. We can conclude that overall nutritive value of ST was lower than FMS, hence, ST is recommended for feeding as an alternate dry fodder under scarcity situations.